A Novel Practical Synchronization Control Approach For A Twin-Axes Table Driven System In Industrial Transportation - Chong, Shin Horng; Hassan, Mohd Khair; Loh, Ser Lee; Md Nawawi, Mohamad Riduwan; Selamat, Hazlina (UTeM, 2019)
Motion synchronization in multiple number of axes or motors has drawn much attention, especially in modern manufacturing development for high speed industrial transportation. As load weight to be driven becomes heavier, multi-axis table drive system is necessary needed. In multiaxis table drive system, the synchronization error disturbs high precision motion. Meanwhile, the fast response time of the synchronization control will cause serious vibration too. It is caused by a motion error due to a characteristics change of a table slide system. Many advanced controllers such as cross-coupling, fuzzy-logic coupling, and predictive synchronization error compensation have been proposed to achieve high positioning performance of synchronous motion. However, above-mentioned controllers require known model parameter and deep understanding of control theory. In this project, the main objective to be achieved is to successfully proposing a practical synchronous control that emphasizes a simple design procedure that does not acquire plants parameter modeling, and yet is able to demonstrate high robustness and accuracy performance for a twin-axes table driven system. The practical synchronous control approach adopts nominal characteristic trajectory following control as the feedback controller, and incorporated with an acceleration feedforward compensation. The nominal characteristic trajectory following control has been proved its advantageous in demonstrating high positioning and robust performances for a single-axes table, but not for the twin-axes table driven system. In addition, another novel algorithm in the controller is the incorporation of the acceleration feedforward compensation that useful to reduce the synchronization error. The project will begin with the construction of twin-axes table driven system that used to clarify the usefulness of the proposed control strategy. The effectiveness of the proposed method is confirmed through numerical and experimental validation. The success of this research will provide practical solution to motion synchronization field and therefore provide a great advantage to be applied in industry.